Pap smear screening: a retrospective study - Soni, Anjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cervical cancer is the seventh cancer in overall frequency, but the second most common cancer among women worldwide. The objective was to study the population undergoing pap-smear screening. Methods: It is retrospective study conducted in general hospital, GMERS Medical College Gotri, Gujarat, India. Total 1003 patients who attended OPD have undergone routine pap smear screening over period of 6 months from January 2016 to June 2016. Cytotological examination was done and test results were classified according to Bethesda system. Results: Abnormal tests were found in 36 patients. Conclusions: Pap smear a routine screening test offered to every woman who comes to our OPD irrespective of her complaints. Every woman at least once in her lifetime should go for pap-smear examination. It is effective screening test for cervical carcinoma. It is cost effective test with high specificity and very easy to perform so it becomes the method of choice for cervical carcinoma screening. With proper follow up patients with abnormal tests are screened and appropriate treatment is being offered to patients.